METODE TOPSIS SISTEM PENDUKUNG KEPUTUSAN DALAM MEMILIH MURID PAUD TELADAN - Tri Rahayu; Erly Krisnanik; Anita Muliawati (Jurnal Teknologi Informasi dan Pendidikan, 2020)
In determining the decision needed an appropriate and fast method. One of them is the method that will be used in this research, the TOPSIS Method. in this case determine the assessment of student kindergarten model will be processed by the method. The first stage is to determine the criteria namely; creative, good manners, flexibility of speech, discipline and honesty. then each criterion is given a weight which is processed by the TOPSIS method. The importance of the criteria is determined by the assessment team or the teacher who is considered an expert here. After the weighting of the criteria evaluation is then conducted a validation test or competency test that determines whether or not the criteria are met. If it is feasible, student data can be made to determine the students' role models. The of student kindergarten are not students who are smart based on academics but rather are characteristic. Where the characteristics of education from an early age is very important to determine the development of a child's soul into a man of good character. From the results of the study as a recommendation to determine the assessment of student kindergarten can use the TOPSIS method. The results of calculations with the topsis method determine the criteria of the student kindergarten, the results are: M. Reyhan (4.009), M. Hilmansyah (1.220), Cindy Clarisa (1.139), Michael (0.560) and Alika (0.516). So that the highest preference in determining pupils or role models is M. Reyhan and the lowest is Alika.